EPIDEMIOLOGY AND CONTROL OF GASTROINTESTINAL NEMATODES OF BUFFALO IN BALOCHISTAN - M. Ramzan; N. Ahmad; K. Ashraf; K. Saeed; A. Z. Durrani; S. Jan; Rafiuddin; M. A. Khan (Journal of Animal and Plant Sciences, 2017)
A study was conducted to assess the epidemiological and control aspects of gastrointestinal nematodes of buffalo at Quetta, Balochistan, from March 2012 to February 2013.A total of 300 faecal sample (25sample per month) were examined during the study period. Faecal analysis showed overall nematodes prevalence as 33.99%. Haemonchosis was recorded with higher prevalence. Buffalo calves˂ 1 year of age presented higher nematodes prevalence than 1-2 years and >2 years of age groups. Female buffalo were infected with nematodes higher than male animals. The nematodes were prevalent almost throughout the year, however a peak infection were recorded during late summer (August).Therapeutic studies showed higher (89-100%) reduction of EPG in buffalo calves treated with Ivermectin followed by Levamisole (88-100%) and Oxfendazole (86-100%). The present study also indicated that no anthelmintics resistance was found against gastrointestinal nematodes infection of buffalo in Quetta. However it is recommended that the proper anthelmintic dose with 5-6 months interval and rotation of anthelmintics for minimize the nematodes infection and enhance buffalo productivity.
Keywords: Gastrointestinal Nematodes; Buffalo; Quetta; Balochistan; Pakistan